High School Geometry Learning for Cimahi Mathematics MGMP Teachers Using GeoGebra - Hedi; Sri Nur Yuliyawati; Anny Suryani; Iis Sulyaningsih (ReTII, 2022)
Mathematics learning is often complained about by most high school teachers because it is not able to attract students’ interest. This can be overcome by applying mathematical software so that it has a positive impact on increasing student interest in learning. In this regard, "Learning Geometry Using GeoGebra" was carried out for the Mathematics MGMP of SMA Negeri Cimahi. The purpose of this training is to improve the skills and knowledge of SMA Cimahi teachers in delivering geometry material using GeoGebra. This training was attended by 25 teachers who are members of the Mathematics MGMP of SMA Cimahi. The training was held face-to-face at SMA Negeri Cimahi for 40 hours with a duration of five weeks. The results of this training show the topic of determining "Parallel Lines, Perpendicular Lines, Triangles, and Quadrilaterals", all participants are very familiar with the use of Geogebra. On the topic of Determining "Area, Point Distance, Field Distance, Angle, and Volume", almost all participants are very good at using Geogebra and only a few participants are not good at it. On the topic of making pictures and animations â€œCube, Block, and Limasâ€, most of the participants were very good at it, there were some participants who mastered it and only a small part still lacked it. Thus, this training has increased the competence of the trainee mathematics teachers in operating the GeoGebra software in Geometry learning. This is very supportive of the mathematics learning process in the class he teaches so that the students are enthusiastic. Keywords: geometry, mathematics, GeoGebra